Industry structure and market performance of the Malaysian construction industry - Ab Aziz, Nurul Afifah (2015)
The construction sector is one of the important sector in the Malaysian economy in terms of its contribution to the Gross Domestic Product (GDP). This study analyse the industry structure and its performance using the Structure-Conduct Performance paradigm approach. The market concentration measurements, measures namely; Concentration Ratio (CR), Herfindahl Hirschman Index (HHI), Hanna and Kay Index (HK), Entropy Index (EI), and GINI Coefficient (GINI). Economic profit is used to determine the relationship between the industry structure and its performance. The profitability of an industry is considered as average rate of return on capital which will evaluate industry performance. The profitability of the industry has shown high correlation with the market concentration and market share. This study estimate from year 2000 until 2012 and data obtained from the annual report of the construction firm’s listed in Kuala Lumpur Stock Exchange Market (BURSA Malaysia). Panel data analysis estimation results showed that the random effect model is the most appropriate model. For this period, CR4 and CR8; HHI; HK; and GINI, shows that the construction industry is moving towards a concentrated market structure and indicative of oligopoly market. The Entropy index shows that the industry is moving towards the noncompetitive market. Results from panel data regression shows that the market share and market concentration are significant in determining the profitability of the large firm. The entry barrier is also found to be significant as represented by the positive effect of market concentration and market share. We concluded that the construction industry has an oligopolistic characteristic with less number of firms, and high profitability due to high degree of concentration level. Empirical findings have provided some basis of the industry structure based on the determination of concentration level in the Malaysian construction industry. The result can bring some amendments to the policy measure in order to ensure that the market structure does not involve monopolistic practices. Many factors which influence the non-competitive market structure, such as the absence of the policy implementation and do the policy favour the potential of dominant firm. This analysis can provide some regulation and policy implications that are parallel with the government’s objective in ensuring a more competitive industry in the economy as a whole.